Export opportunities of Indian potatoes - Chakrabarti, S K; Singh, Brajesh; Sharma, Sanjeev (Indian Horticulture, 2020)
India contributes around 13% of the total world potato production but our contribution to world potato export is around 1.6% only, which is not even 1% of the total potato production in the country. Potato being semi-perishable and bulky agri-commodity, its export from India was not guided by a long term policy support. As potato is a politically sensitive crop, targeted steps are usually taken to keep its retail price at an affordable level for the domestic consumers. Therefore, potato export was, in general, a crisis management tool during the years of oversupply. On the contrary, in the international markets exports can only be increased through building credibility and making long term contracts.